Phase formation, dielectric and ferroelectric properties of Mn, Al Doped BCZT ceramics by molten salt method - Intatha U. (Taylor and Francis Ltd., 2015)
Lead-free Ba(1-x)CaxZr0.1Ti 0.9O3 (x = 0.15) ceramics doped with 0.00-0.20 mol% MnO2 and Al2O3 were prepared by the molten salt method. The powder was ball-milled for 24 h and then calcined at 1000°C for 4 h and sintered at 1300°C for 2 h. The phase formation and dielectric properties of the ceramic systems were analyzed by X-ray Diffraction (XRD) and electrical measurement. The phase of the samples showed pure perovskite structure for all conditions. The BCZT ceramics doped with MnO2 and Al2O3 exhibited a dielectric properties. BCZT doped with Mn has a higher dielectric constant than BCZT doped with Al. The loss tangent values at 1 kHz were lower than 0.02 of all samples. The ceramic systems indicate ferroelectric behavior for all samples (Pr ∼ 1.25-2.26 μC/cm2and Ec ∼ 3.10-4.25 kV/cm). Copyright© Taylor and Francis Group, LLC.